eCM 2021
DOI: 10.22203/ecm.v041a50
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-mediated interactions with a laminin-presenting substrate modulate biosynthesis and phenotypic expression for cells of the human nucleus pulposus

Abstract: With aging and pathology, cells of the nucleus pulposus (NP) de-differentiate towards a fibroblast-like phenotype, a change that contributes to degeneration of the intervertebral disc (IVD). Laminin isoforms are a component of the NP extracellular matrix during development but largely disappear in the adult NP tissue. Exposing human adult NP cells to hydrogels made from PEGylated-laminin-111 (PEGLM) has been shown to regulate NP cell behaviors and promote cells to assume a biosynthetically active state with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
(140 reference statements)
0
10
0
Order By: Relevance
“…At least 15 Laminin isoforms are formed by the combination of three different peptide chains, and multiple Laminin isoforms and their receptors are expressed in IVD tissues [38]. In addition, integrin-mediated interaction with Laminin regulates the phenotype of NP cells [39].…”
Section: Non-collagenous Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 15 Laminin isoforms are formed by the combination of three different peptide chains, and multiple Laminin isoforms and their receptors are expressed in IVD tissues [38]. In addition, integrin-mediated interaction with Laminin regulates the phenotype of NP cells [39].…”
Section: Non-collagenous Proteinsmentioning
confidence: 99%
“…Available evidence suggests that the response of nucleus pulposus cells to sustained mechanical stimuli is closely related to disc degeneration [16,56]. Furthermore, alterations in ECM composition modulate NP cell behavior by directly affecting cell-ECM interactions without altering the mechanical environment [39,57]. Dysregulation of ECM homeostasis is closely related to the process of disc degeneration, and proteolysis of the ECM occurs at the beginning of this process.…”
Section: Ecm Dysregulation In Iddmentioning
confidence: 99%
“…According to their expression levels, integrins expressed in human IVDs can be divided into five groups ( Fig. 4 ): high expression group ( α 1, α 5, α v, β 1, β 3, β 5), low expression group ( β 2, β 4, β 6), controversial expression group ( α 2, α 3, α 6), no expression group ( α 4, α IIb) and expression unexplored group ( α 7, α 8, α 9, α 10, α 11, α D, α E, α L, α M, α X, β 7, β 8) 116 , 117 , 118 , 119 , 120 , 121 , 122 . In the controversial expression group, previous study showed that integrins α 2, α 3, α 6 were not expressed in human IVD tissues 116 , but some studies demonstrated that they could be detected in human NP tissues and cells 120 , 121 , 122 .…”
Section: Focal Adhesion Proteins In Intervertebral Discmentioning
confidence: 99%
“…A study reported that a series of laminin‐mimetic peptide poly(ethylene) glycol (PEG) hydrogels modulated integrin and syndecan binding in NP cells, thus promoting ECM biosynthesis [ 76 ] primarily through integrin α 3 mediated interaction with laminin, which also associated with phosphorylation of signaling molecules of extracellular‐signal‐regulated kinase (ERK1/2) and glycogen synthase kinase (GSK3 β ). [ 77 ]…”
Section: Rationale Precision Biomaterial‐based Tissue Engineering Tar...mentioning
confidence: 99%